Analisis Konten Pesan Dakwah dalam Web Series Ustad Milenial Episode 1-4 - Rahmatia Tajudin; Nia Kurniati; N. Sausan M. Sholeh (Bandung Conference Series: Islamic Broadcast Communication, 2023)
Abstract. This research is motivated by the development of increasingly widespread electronic media. This makes it easier for da'i to convey da'wah messages, one of which is through short films. This study uses content analysis from Creswell, data collection techniques through observation and descriptive documentation with a qualitative approach. The purpose of the research is to find out the da'wah messages contained in the Millenial Ustad Web Series episodes one to four. The results of the Millenial Ustad Web Series research in episodes one to four, there are three Da'wah messages which include the message of Akidah containing faith in Allah SWT and faith in God. God's decree or destiny. The message of Sharia in this study includes worship, muamalah and Islamic law, such as the obligation to wear the hijab, stay away from usury and the prohibition of bribery. The moral message in this study is the obligation to be filial to parents. Abstrak. Penelitian ini dilatarbelakangi oleh perkembangan media elektronik yang semakin luas, hal tersebut memudahkan da’i dalam menyampaikan pesan-pesan dakwah salah satunya melalui film pendek. Penelitian ini menggunakan analisis isi dari Creswell, teknik pengumpulan data melalui observasi dan dokumentasi bersifat deskriptif dengan pendekatan kualitatif. Adapun tujuan penelitian mengetahui pesan-pesan dakwah yang terdapat dalam Web Series Ustad Milenial episode satu sampai empat. Hasil penelitian Web Series Ustad Milenial pada episode satu sampai empat ini, terdapat tiga Pesan Dakwah yang meliputi pesan Akidah berisi tentang beriman kepada Allah SWT dan beriman kepada ketentuan atau takdir yang ditetapkan Allah. Pesan Syariah dalam penelitian ini meliputi ibadah, muamalah serta hukum islam seperti kewajiban menggunakan hijab, menjahui riba dan larangan suap menyuap. Pesan Akhlak dalam penelitian ini yaitu kewajiban berbakti kepada orang tua.